Endoscopic treatment of Bouveret syndrome with a combination of electrohydraulic lithotripsy and balloon expansion: A case report. Issue 1 (27th March 2023) - Watanabe, Kotaro; Kawai, Hirokazu; Sato, Toshifumi; Natsui, Masaaki; Inoue, Ryosuke; Kimura, Mayuki; Yoko, Kazumi; Sasaki, Syun‐ya; Watanabe, Masashi; Tsukada, Yoshihisa; Terai, Shuji
Abstract: Bouveret syndrome is a rare type of ileus caused by the impaction of gallstones passing through a cholecystoenteric fistula in the duodenum. Endoscopic treatment with minimally invasive procedures is preferable for patients with this syndrome, typically for elderly individuals with a high surgical risk. Conventional endoscopic techniques often fail to remove impacted stones that are generally large and occasionally solid. We report the case of an 88‐year‐old bedridden woman with severe dementia who presented with difficulty in breathing. The patient was diagnosed with aspiration pneumonia. In addition, computed tomography showed a cholecystoduodenal fistula and a gallstone 37 mm in diameter that impacted the duodenal bulb. Bouveret syndrome was diagnosed on the basis of the computed tomography findings. The impacted stone was too large and hard to split with standard endoscopic lithotripsy using grasping forceps, mechanical lithotripter, polypectomy snare, basket catheter, and electrohydraulic lithotripsy (EHL). However, EHL with a dual‐channel therapeutic endoscope was achieved to drill a narrow hole approximately 20 mm deep into the stone, in four sessions. The stone was subsequently split by inflating the balloon, which was inserted into the hole, to 10 mm in diameter at 3 atm. All the split stones were spontaneously excreted during defecation after a few days. If the gallstone is too hard to fragment by endoscopic EHL alone, a combination of EHL and balloon expansion might be a useful alternative.